Detection of Human Herpes Viruses CMV, EBV, and HHV6 and their co-infection in renal and allogeneic hematopoietic stem cell transplant recipients by multiplex real-time PCR - Hasan, Nazmul; Rahim, Rummana; Hasan, Abu; Mohammad Saleh, Abu Jafar; Rahman, Mizanur (Pulse, 2024)
Background: Herpesviruses infection especially Cytomegalovirus (CMV) in transplant recipients cause life-threatening diseases. Furthermore, their management may be complicated by co-infection with other human herpes viruses like Epstein-Barr Virus (EBV) and human herpes virus 6 (HHV6). Besides CMV, no data is available for EBV and HHV6 in transplant recipients in the country. Study Population: The study included 48 renal transplant recipients, and 36 allogenic hematopoietic stem cell transplant (allo-HSCT) recipients treated at Evercare Hospital in Dhaka, Bangladesh, between February 2015 and November 2023. Materials and method: The transplant recipients were advised to undergo CMV, EBV, and HHV6 PCR tests based on recommendations from nephrologists and hematologists. The diagnostic method used was multiplex real-time PCR, which allows for the simultaneous detection of multiple pathogens in a single test. Results: In renal transplant recipients, 43.75% tested positive for herpesvirus infections. Among them, 35.42% had CMV as the sole infection, while 8.33% had co-infections involving CMV, EBV, and HHV6. In allo-HSCT recipients, 88.89% tested positive for herpesvirus infections. Of these, 58.33% had CMV as the only infection, 11.11% had HHV6, and 19.45% had co-infections with CMV, EBV, and HHV6. Interestingly, no cases of EBV infection as a single pathogen were found in either group of patients. Thus, this study suggests that after renal and allo-HSCT transplant procedures, multiplex real-time PCR for CMV, EBV, and HHV6 may be valuable for the further management of these patients and warrants large scale study. Pulse Vol.16, 2024 P: 15-21